(untitled) (Colombia Medica, 2007)
Male hypogonadism represents an altered testicular function with infertility and decreased testosterone production. It can be caused by an intrinsic testicular damage, hypothalamic-pituitary dysfunction, or decreased end organ response to testosterone. Signs include hair loss, decreased sexual function, voice changes, eunuchoidal habitus and gynecomastia. The testes are small and osteoporosis may be present. The diagnosis is suspected clinically and is confirmed with decreased circulating testosterone concentrations. FSH and LH are increased in patients with testicular damage (primary hypogonadism) and decreased in those with hypothalamic–pituitary dysfunction. Testosterone is available for intramuscular injection, transdermic patches, gel or pellets and by absorption by the oral mucosa.